1854 Wash. Sess. Laws 80, An Act Relative to Crimes and Punishments, and Proceedings in Criminal Cases, ch. 2, § 30. - (:unkn) unknown (General Publisher, 1854)
Prohibited exhibiting, in a rude, angry, or threatening manner, a pistol, Bowie knife, or other dangerous weapon. Punishable by imprisonment up to 1 year and a fine up to $500.
--
Keywords: BRANDISHING